ANALISIS KANDUNGAN LOGAM BERAT Pb DAN Cd DI MUARA SUNGAI MANGGAR BALIKPAPAN - Dewi, Godfrida Any Yusriana; Samson, Steven A; Usman, Usman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 12 No 2 (2018)DO - 10.24843/EJES.2018.v12.i02.p02, 2018)
Human activities around the estuary of the Manggar river in Balikpapan produce waste disposal and cause heavy metal contamination such as lead (Pb) and cadmium (Cd) in water bodies. The contaminant can endanger the life of aquatic organisms. It can also occurs heavy metal bioaccumulation in the body of the aquatic organisms. The results show that the heavy metal content of Pb and Cd in water, sediment and water biota indicated that the estuary of the Manggar River was contaminated by heavy metals. The content of Pb and Cd in water is 0.276 mg/l and 0.020 mg/l, in sediments is 24.7 mg/kg and 4.52 mg/kg, and in the biota is 4.20 mg/kg and 0.80 mg/kg. This means that fish and shells taken from the waters around the estuary of the Manggar River are not safe for consumption because they can interfere the human health.